Dukungan Keluarga dan Kecemasan Pada Penyitas Covid-19 - Kumala Sari, Citra Ayu; Zakiyah, Lailatuz; Syafi’i, Imam (Universitas Darul Ulum, 2023)
Covid-19 had a psycological impact on the Indonesia people, especially in Tulungagung. one of the psycological effect experienced in anxiety. Covid-19 survivors are easily suffering a susceptible to anxiety. But some theories suggest that anxiety can be overcome by providing family support. This study was aimed at identifying the relationship between family support and anxiety for COVID-19 survivors in Tulungagung. The method used is quantitative correlation with the total population, namely Covid-19 survivors as of July 2021, which are 3389 people. From this population, a accidental sampling technique was used with the criteria for Covid-19 survivorship with a 10% probability sampling, and obtained sample of 251 people. The data analysis technique used is the Spearman Rho correlation test (non-parametric). The results showed that there was a correlation between the variables of family support and anxiety which was indicated by a significance of 0.00 with a strong negative relationship, indicated by the correlation coefficient of -0.608. This relationship means that if the family support variable increasses, the level of anxiety variable will decrease, vice versa. The results of the study are expected to be able to become a deeper reference for similar research and are expected to be able to serve as a guideline for the front line of health overcoming Covid-19 in curing patients, especially tackling the patient's level of anxiety.